DIPLOMASI INDONESIA TERHADAP UNI EROPA DI WORLD TRADE ORGANIZATION (WTO): Studi Kasus Pelarangan Ekspor Bijih Nikel Mentah Tahun 2019-2022 - Muhammad Bimo Tangguh Bagassetyo, (2023)
This thesis discusses Indonesia's diplomacy towards the European Union at the World Trade Organization (WTO) with a focus on the ban on raw nickel ore exports implemented by Indonesia in the period 2019 to 2022. This study uses theories and concepts including, diplomacy theory, the concept of trade disputes and downstream concept. The purpose of this study is to analyze the diplomatic efforts implemented by Indonesia in dealing with this dispute with the European Union at the WTO. The research method used in this thesis is descriptive qualitative research with a case study approach. Research data were obtained through literature review, analysis of official documents, and primary sources relevant to the research topic. The results of the study show that Indonesia has used diplomacy in efforts to resolve disputes at the WTO to deal with this dispute with the European Union. Indonesia has also tried to maintain its policy of banning the export of raw nickel ore with the argument of developing domestic downstream industries and adding value to domestic resources. The impact of Indonesia's diplomacy towards the European Union in this dispute has complex implications. On the other hand, Indonesia's diplomacy has maintained a policy of banning the export of raw nickel ore which is considered important for the development of the downstream nickel industry in the country. However, the impact on bilateral relations between Indonesia and the European Union is still a concern. This research provides an understanding of how Indonesia's diplomacy deals with disputes with the European Union at the WTO regarding the banning of raw nickel ore exports.